Theatre within the Theatre, Play within the Play— Self-Reflexivity in Jim Nolan’s Blackwater Angel - Bertha, Csilla (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Jim Nolan’s Blackwater Angel (2001) employs a metadramatic approach, intertwining two types of play-within-the-play to enhance self-reflexivity. The external play portrays the fate of seventeenth-century healer Valentine Greatrakes, evoking the concept of theatrum mundi, while the inset play, The Broken Heart, influences the main characters and plot. Boundaries between the two plays blur as characters interact, emphasizing role-playing within and outside of theatrical reality. This dual reality reflects Ubersfeld's notion of theatre as a "(two-fold) referent," embodying both physical presence and symbolic representation. Play-within-the-play serves as a meta-theatrical strategy, facilitating self-reflection and exploration of identity, particularly relevant in the postmodern era's emphasis on intertextuality and self-reference.